Phenological pattern of fifteen Mediterranean phanaerophytes from shape Quercus ilex communities of NE-Spain (Plant Ecology, 1998)
The phenological pattern of ﬁfteen Mediterranean phanaerophytes has been studied in several sites per species, by visiting the populations on a monthly basis over a one year period. Studied phenophases were dolichoblast vegetative growth (DVG), ﬂower bud formation (FBF), ﬂowering (F), fruit setting (FS), seed dispersal (SD), and leaf shedding of dolichoblasts (LSD). Considering the whole set of species, DVG, FBF and F took place mainly in spring, FS in summer, SD in autumn and LSD in summer and in autumn. Interspeciﬁc comparisons showed a wide variety of phenological patterns, which have been sorted according to the ‘phenophase sequence index’ (PSI). This index quantiﬁed the degree of superposition between DVG, FBF and F, and it constituted the basis for a functional classiﬁcation of phenological patterns. Two groups were established. The ‘type I’ group was characterised by the concentration of phenophases in a short time in spring, while the ‘type II’ by the protraction and sequential arrangement of phenophases. Type I species performed most of their functions during a resource surplus period, but they have to face an intraplant competition between vegetative and reproductive demands. Type II species avoided intraplant competition but had to develop part of DVG, FBF and F during sub-optimal periods. It is hypothesised that type I species possess deeper roots, rely on predictable water sources and occupy mature stages of succession. Type II species, on the contrary, are expected to depend on more unpredictable water sources, to possess shallower root systems and to colonise earlier stages of succession. Intraspeciﬁc variability of phenology was found to be low among populations of the same species. Bud structure, which is a phylogenetic trait, may exert important constraints on plant phenology